Effect of Exchange Rate System on the Demand for and the Composition of International Reserves in Developing Countries - Asadollah Farzinvash; Soheila Biria (پژوهشهای اقتصادی, 2010)
The aim of this paper is twofold. It first investigates the demand for international reserves using panel data for 32 developing countries during the period 1975 – 2004. To this end, an Error Correction Model (ECM) approach is employed to estimate the empirical model and then a capital asset pricing model (CAMP) is used to determine the composition of the foreign exchange reserves. A dummy variable is included in the model to consider the effect of changing exchange rate system on the demand and the composition of international reserves. The results show that there is a negative relationship between exchange rate flexibility and the demand for international reserves.